Investigating the relationship between body roundness index and low muscle mass based on a cross-sectional study: Focus on visceral adipose tissue - Wei Huang; Huangyi Yin; Bijun Yang (PLoS ONE, 2025)
Background The relationship between body roundness index (BRI) and low muscle mass (LMM) remains unclear. This study investigated their association in American adults under 60 years. Methods This secondary analysis utilized de-identified data from the National Health and Nutrition Examination Survey (NHANES, 2011–2018; n = 8,065 adults <60 years). Multivariable logistic regression evaluated associations between BRI and LMM, while multivariable linear regression assessed relationships between BRI and appendicular skeletal muscle mass (ASM)/BMI. Restricted cubic splines (RCS) tested nonlinearity, and receiver operating characteristic (ROC) curves compared BRI’s predictive performance against other body measurements indices. Finally, to assess the robustness of results, we conducted subgroup and sensivity analysis. Results Each 1-unit BRI increase elevated LMM risk by 73% (OR=1.73, 95%CI = 1.61–1.86, p < 0.0001). Participants in the highest BRI quartile had 69-fold higher LMM odds versus the lowest quartile (OR=68.96, 95%CI = 33.62–141.47). RCS analysis revealed nonlinear positive BRI-LMM associations. Each10 units increase in BRI, ASM/ BMI decreased by 29% (β = −0.29,95% CI: −0.31, −0.28, p value < 0.0001). Participants in the highest BRI quartile had significantly lower ASM/ BMI levels, with corresponding β values of − 0.17. RCS analysis revealed nonlinear negative BRI- ASM/ BMI associations. When compared to other body measurements index, BRI shows good performance in identifying individuals at risk of LMM(AUC = 0.835).And sensitivity analyses confirmed robustness. Conclusion Higher BRI may increase the risk of LMM in individuals under 60 years old among Americans, especially in men. BRI may serve as a supplementary indicator for identifying individuals at risk of LMM.